2005
DOI: 10.1007/s00247-005-1541-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quiet breathing and controlled ventilation in the high-resolution CT assessment of airway disease in infants with cystic fibrosis

Abstract: In infants with CF, fully inflating the lung improved the ability to diagnose early BE, and obtaining motion-free images at end exhalation enhanced the detection of AT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…These gating techniques are already being applied in human studies and will become more prevalent as scanner technology allows visualization of larger and larger volumes of the lung with each acquisition (20). However, even static whole lung images obtained from helical scans during breath-holds at two volumes will yield useful results (7) and provide a unique description of regional lung static mechanical properties that could be applied clinically to quantitate regional lung properties in patients already receiving this type of imaging, such as patients with severe emphysema being considered for lung volume reduction surgery or cystic fibrosis (2,5,17).…”
Section: Discussionmentioning
confidence: 99%
“…These gating techniques are already being applied in human studies and will become more prevalent as scanner technology allows visualization of larger and larger volumes of the lung with each acquisition (20). However, even static whole lung images obtained from helical scans during breath-holds at two volumes will yield useful results (7) and provide a unique description of regional lung static mechanical properties that could be applied clinically to quantitate regional lung properties in patients already receiving this type of imaging, such as patients with severe emphysema being considered for lung volume reduction surgery or cystic fibrosis (2,5,17).…”
Section: Discussionmentioning
confidence: 99%
“…The most important variable that requires standardisation during CT scanning is lung volume [26]. Most young children are not able to do a voluntary breath hold at the correct volume level and at the correct moment.…”
Section: Chest Ctmentioning
confidence: 99%
“…In a study of infants with ''new'' nCLD, MAHUT et al [33] reported a dissociation between airway function, as measured by maximal flow at function residual capacity, and computed tomographic abnormalities, suggesting a decreased airway involvement in the pathology of ''new'' nCLD. Studies combining new lung imaging approaches in young children [34] and lung function methods sensitive to peripheral mechanics, such as FOT, are required to address these issues in detail. In particular, techniques capable of determining alveolar surface area in vivo are likely to be informative.…”
Section: Resistance and Reactancementioning
confidence: 99%